Immunotherapy improved cancer related pain management in patients with advanced Hepato-Pancreatic Biliary Cancers: A propensity score-matched (PSM) analysis - Wu, Xiufang; Qin, Fei; Zhang, Qiangze; Qiao, Jianling; Qi, Yulian; Liu, Bing (Frontiers in Oncology, 2022)
Background Hepato-pancreato-biliary (HPB) cancer is a serious form of cancer. in many HPB cancers, including cholangiocarcinoma (also known as bile duct cancer), pancreatic cancer, hepatocellular carcinoma, gallbladder cancer and ampullary cancer, although several treatment options are developed during these decades, the prognosis is still poor. Methods A total of 356 HPB cancers patients in advanced stage received different kinds of treatments including adjuvant chemotherapy, radiotherapy, immunotherapy and best supportive care. Among these patients with advanced HPB cancers, 102 patients have received standard opioid treatment for pain controlling. Results A total of 325 patients were identified from the DEPARTMENT OF MEDICAL ONCOLOGY, JINAN PEOPLE’S HOSPITAL. Multivariable Cox regression analysis demonstrated that age (HR 1.828, 95% CI 1.251-2.246; P=0.007), serum CA-19-9 ≥ 37U/ml (HR 1.602, 95% CI 1.187-3.258; P=0.015), tumor size (HR 2.278, 95% CI 1.405-4.368; P=0.003), nodal status (HR 1.309, 95% CI 1.108-2.439; P=0.032), and R1 tumor resection (HR 1.481, 95% CI 1.049-2.091; P=0.026) were independent factors associated with OS. A nomogram that incorporated these significant prognostic factors was established. The calibration plots demonstrated high concordance between predictive nomogram values and actual OS for 1-year, 3-year, and 5-year OS. The model demonstrated excellent discriminatory power in both the DEPARTMENT OF MEDICAL ONCOLOGY, JINAN PEOPLE’S HOSPITAL and MSK cohorts, with adjusted C-index values of 0.729 and 0.712, respectively. Conclusion In this report, we confirmed that immunotherapy improved cancer related pain management in patients with advanced Hepato-Pancreatic Biliary Cancers